2022
DOI: 10.1186/s12957-022-02596-0
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic role of tumor size in stage T1 gastric cancer

Abstract: Background The purpose was to assess the contribution of tumor size to the prognosis of patients with gastric cancer. Methods Patient data were sourced from the Surveillance, Epidemiology, and End Results program (SEER) database. Cox proportional risk regression was performed to determine the prognostic role of tumor size. Kaplan-Meier curves were conducted to calculate survival curves. Consistency index (c-index) and subject exercise curve (ROC) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 32 publications
2
7
2
Order By: Relevance
“…We only performed TLDG in patients with clinically early gastric cancer, with the majority of cases in cT1 and the cT2 stage (94.5%) and endoscopic tumor size principally < 3 cm (66.3%). Yan Chen et al's study on the early gastric cancer patient group also recorded similar results [3]. Tumor size has been evaluated by many authors as a crucial factor in predicting postoperative stage and long-term outcomes after gastric cancer surgery [3,4].…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…We only performed TLDG in patients with clinically early gastric cancer, with the majority of cases in cT1 and the cT2 stage (94.5%) and endoscopic tumor size principally < 3 cm (66.3%). Yan Chen et al's study on the early gastric cancer patient group also recorded similar results [3]. Tumor size has been evaluated by many authors as a crucial factor in predicting postoperative stage and long-term outcomes after gastric cancer surgery [3,4].…”
Section: Discussionmentioning
confidence: 78%
“…Yan Chen et al's study on the early gastric cancer patient group also recorded similar results [3]. Tumor size has been evaluated by many authors as a crucial factor in predicting postoperative stage and long-term outcomes after gastric cancer surgery [3,4].…”
Section: Discussionmentioning
confidence: 78%
“…Furthermore, there were a few researchers studied the predicting value of tumor size was influenced by T stage in colon cancer, esophageal cancer and gastric cancer [ 6 , 29 31 ]. Dai et al found in colon cancer that when T stage increased, the influence of tumor size on death and recurrence risk decreases gradually [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al found in esophageal cancer that tumor size had the strongest effect on prognosis for T1 classification and the weakest effect for T4 classification [ 30 ]. Chen et al declared that tumor size showed superior the discriminatory ability at T1 stage [ 31 ]. While Chen et al only take a few factors into analyses and didn’t mention the clinical significance based on DCA curves.…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al reported that tumor size can be included in AJCC staging, considering that it may have different prognostic roles in gastric cancer at different stages (6). In some series, it has been shown that MLN size is effective in the determination of the prognosis and it provides valuable support to the classification systems in patients with gastrointestinal malignancies, including colon and esophageal cancer (7,8).…”
Section: Introductionmentioning
confidence: 99%